Importance of second language in the tourism sector (2015)
In the present work we aim to show the importance of awareness among tourism businesses to train all linked to the tourism sector in the management of the English language staff, the above given the steady growth of foreign visitors to our country. The national government seeking to promote and implement strategies to provide competence in the English language created the Colombia National Bilingualism Program 2004 - 2019 " English as a Foreign Language : A strategy for competitiveness" . In order to meet the specific goals of the program the Ministry of Commerce, Industry and Tourism, started in 2012 the training program to all persons belonging to the tourism sector